Dynamical chaos rise in the system of large number of nonlinear coupled oscillators - Buts, V.A.; Kovalchuk, I.K.; Tarasov, D.V. (Вопросы атомной науки и техники, 2007)
The problem of dynamical chaos arising in distributed systems is considered. It was shown that in many cases it is possible to allocate relatively isolated subsystem which may be simpler for investigation. We suppose that chaos in this subsystem leads to chaotic behavior of all system. Besides, the allocated subsystem may be used for describing complex dynamics of nonlinear three-wave interaction, in particular, in plasma systems. The analytical criterion of arising dynamics chaos in distributed system was obtained. This criterion was confirmed by numerical simulation.